A Strategic Management Analysis To Enhance Organizational Effectiveness: A Case Study Of The Rupiah Banknote Printing Industry: Analisis Manajemen Strategis untuk Meningkatkan Efektivitas Organisasi: Studi Kasus Industri Percetakan Uang Kertas Rupiah - Alam, Sandi; Danang Aziz Akbarona; Mulyani, Sri (OGZ Research & Publishing, 2026)
Objective : This study examines strategic management practices and challenges in enhancing organizational effectiveness within the Indonesian rupiah banknote printing industry, an environment characterized by strict regulation and high security sensitivity. Methodology : Using a qualitative case study approach, data were collected through in-depth interviews, non-participant observation, and document analysis involving leaders and key employees selected purposively. Thematic analysis was applied through data reduction, data display, and conclusion drawing, supported by triangulation to ensure credibility. Research results : Findings reveal that strategic management is implemented through three core stages: formulation, implementation, and evaluation. Major challenges include limited innovation, resistance to change, regulatory complexity, and weak inter-unit coordination. Despite these constraints, alignment between strategic initiatives and organizational vision contributes positively to operational efficiency, regulatory compliance, productivity, and adaptability to external changes. Overall, effective strategic management strengthens organizational performance in highly regulated public-sector industries.